Análisis de vulnerabilidades del sistema contable blue sky y sus incidencias en el Agroquimicos Alvarado S.A. de la ciudad de Babahoyo - Avendaño Moncayo, Manuel (2019)
Nowadays in all companies it is very important to talk about security in computer systems, due to the increase in threats in TICs. At present, any computer is connected to the internet and is exposed to various threats. The software we are studying in this project has not been the exception, in this case study we have been able to show and witness the different technical flaws of the program that exist in it. This paper reviews some of the techniques and tools currently used for vulnerability detection, some techniques and tools were used that will determine which vulnerabilities and attacks can be reduced with the use of these techniques and tools